2001
DOI: 10.1023/a:1010965013113
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Transcription control systems enable experimental regulation of transgene expression in eukaryotic cells by application of specific repressors or inducers. Currently used inducible systems include tetracycline (tet-off), dimerizer and ecdysone systems. While numerous studies have utilized a single system, their comparative performance under identical conditions remains unclear. We therefore compared the efficiency of these three systems in C6 glioma cells by using transient transfection and the lacZ reporter g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The competitive evaluation of dimerizer-based systems versus alternative methods for regulated gene expression has also been undertaken. In these studies, CID-based systems have shown the highest degree of regulatory selectivity and have consistently demonstrated outstanding dynamic range and sensitivity, particularly as the systems have evolved. ,, The work by Xu et al compared five popular systems for regulating induced gene expression from adenovirus (Ad) vectorsthe tetracycline (Tet-on and T-REx), ecdysone, antiprogestin, and dimerizer based systems . The dimerizer based system tested is an FKBP−FRB complex induced by addition of AP21967, an analog of rapamycin with decreased immunodepressive effects.…”
Section: Application Of Chemically Induced Proximity To Therapeuticsmentioning
confidence: 99%
“…The competitive evaluation of dimerizer-based systems versus alternative methods for regulated gene expression has also been undertaken. In these studies, CID-based systems have shown the highest degree of regulatory selectivity and have consistently demonstrated outstanding dynamic range and sensitivity, particularly as the systems have evolved. ,, The work by Xu et al compared five popular systems for regulating induced gene expression from adenovirus (Ad) vectorsthe tetracycline (Tet-on and T-REx), ecdysone, antiprogestin, and dimerizer based systems . The dimerizer based system tested is an FKBP−FRB complex induced by addition of AP21967, an analog of rapamycin with decreased immunodepressive effects.…”
Section: Application Of Chemically Induced Proximity To Therapeuticsmentioning
confidence: 99%
“…[20] Among the various available gene-switch platforms, the insect ecdysteroidregulated switches are refractory to human endogenous steroids, and typically show very low basal transgene expression, high inducibility, and broad dose-response gradation-usually outperforming other systems in each of these aspects. [21][22][23] The EcR gene switch functions through assembly of 1) the nuclear receptor EcR with a heteropartner protein (the vertebrate retinoid X receptor, RXR, its insect orthologue, the ultraspiracle protein, USP, or a variant); 2) a DNA response element complementary to the DNA binding domains of EcR and the hetero-…”
Section: Introductionmentioning
confidence: 99%